2019
DOI: 10.1039/c9cy00627c
|View full text |Cite
|
Sign up to set email alerts
|

Integrating surface plasmon resonance and slow photon effects in nanoporous anodic alumina photonic crystals for photocatalysis

Abstract: This study explores the potential of gold-coated titania-functionalized nanoporous anodic alumina distributed Bragg reflectors (Au-TiO2-NAA-DBRs) as platforms to enhance photocatalytic reactions by integrating “slow photons” and surface plasmon resonance (SPR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…To provide overview of many functionalities discussed in Sections 4.1-4.7, they are gathered in the Table 2. [190] Gradient-index filters [191] Distributed Bragg reflectors [192] Optical bandpass filters [193] Human protein heavy ions real-time interaction monitoring [194] Tailoring of optical properties with pulse anodization [149] Design of phase shift defect in effective refractive index [195] Hybrid distributed DBRs and apodized GIF photonic structure [196] Characterization of thermotropic ferroelectric liquid crystals confined in the NAA [197][198][199] Glass transition of discotic liquid crystals in one-dimensional fluid [200] Adjustable optical anisotropy by self-assembly of liquid crystals confined in porous structure [201] Sensors NAA template-assisted fabrication of chromium substrate for SERS detection of heavy ions in aqueous solutions [202] Au NPs array on NAA for SERS detection of hemoglobin [203] Controlled fabrication of periodic plasmonic dimer arrays for SERS [204] Graphene-NAA composite for SERS sensing [205] Label-free optical sensor based on interferometric reflectance spectroscopy for TNF-α detection [206] NAA-based interferometer for copper sensing [207] In vivo nanotubes nanotoxicity study on murine model […”
Section: Examples Of Naa Applicationsmentioning
confidence: 99%
“…To provide overview of many functionalities discussed in Sections 4.1-4.7, they are gathered in the Table 2. [190] Gradient-index filters [191] Distributed Bragg reflectors [192] Optical bandpass filters [193] Human protein heavy ions real-time interaction monitoring [194] Tailoring of optical properties with pulse anodization [149] Design of phase shift defect in effective refractive index [195] Hybrid distributed DBRs and apodized GIF photonic structure [196] Characterization of thermotropic ferroelectric liquid crystals confined in the NAA [197][198][199] Glass transition of discotic liquid crystals in one-dimensional fluid [200] Adjustable optical anisotropy by self-assembly of liquid crystals confined in porous structure [201] Sensors NAA template-assisted fabrication of chromium substrate for SERS detection of heavy ions in aqueous solutions [202] Au NPs array on NAA for SERS detection of hemoglobin [203] Controlled fabrication of periodic plasmonic dimer arrays for SERS [204] Graphene-NAA composite for SERS sensing [205] Label-free optical sensor based on interferometric reflectance spectroscopy for TNF-α detection [206] NAA-based interferometer for copper sensing [207] In vivo nanotubes nanotoxicity study on murine model […”
Section: Examples Of Naa Applicationsmentioning
confidence: 99%
“…Lastly, microstructural designs and plasmonic effects expand the light-harvesting range and improve the photocatalytic quantum efficiency. Various plasmonic PCs have been introduced for photocatalysis applications, ranging from water splitting [57] and the mineralization of organic pollutants [58]. A strategy toward the substantial enhancement of hot-electron generation at tunable narrow-band wavelengths using the hybridization of plasmonic and photonic resonance was introduced by Huang et al [53].…”
Section: Hybrid Plasmonic-photonic Photocatalystsmentioning
confidence: 99%
“…Chen et al have proved that overlapping of PBG with bandgap of titania (TiO 2 -coated SnO 2 IO) is the most recommended for activity enhancement, i.e., an increase in the activity in the following order of PBG: 2.55 < 2.98 < 3.35 eV [99]. Moreover, it has been shown that the highest efficiency for dye decomposition has been obtained when PBG overlaps with absorption band of MB (but away from its maximum to avoid the undesired light screening), confirming both dye-sensitization mechanism and slow photon effect [100].…”
Section: Photonic Crystals (Pcs)mentioning
confidence: 71%
“…400-550 nm and PBG at ca. 800 nm [100]. In contrast, Lu et al have succeeded the precise tuning in fabrication of Au-NP/TiO2 PC with LSPR overlapping with the blue edge of PBG, resulting in 2.3-fold higher photocatalytic efficiency for photodegradation of 2,4-dichlorophenol in comparison to the reference Au-NP/nanocrystalline TiO2 under visible-light irradiation [91].…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation